Three way catalytic converter reactions aspects at near ambient temperatures on modified pd-surfaces - Roy, Kanak; Jain, Ruchi; Ghosalya, Manoj Kumar; Reddy, Kasala Prabhakar; Gopinath, Chinnakonda S. (Comptes Rendus Chimie, 2016)
The dissolution of oxygen in palladium plays an important role in palladium catalysis. The present study shows that the surface modification (SM) due to the dissolution of atomic oxygen into the subsurfaces of palladium can be used as a control to tune its catalytic activity. CO oxidation and NO + H-2 + O-2 reaction was separately carried out on metallic Pd and on surface modified Pd using a molecular beam instrument and the results were compared. The metallic Pd does not show activity below 400 K for both reactions, whereas the SM-Pd shows activity at near-ambient temperatures. The electronic change due to SM was investigated using ambient pressure photoelectron spectroscopy, and the investigation clearly shows the effect of subsurface oxygen in the ambient temperature activity of palladium. (C) 2016 Academie des sciences. Published by Elsevier Masson SAS. All rights reserved.